2013
DOI: 10.1179/1476830513y.0000000068
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of reflex maturation and physical development in suckling rats: effects of a maternal diet containing lipids from goat milk

Abstract: The supply of goat's milk offered to Wistar rats during pregnancy and lactation provided a variety of fatty acids necessary to accelerate the development of offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
2
9
0
5
Order By: Relevance
“…The body weight of neonates treated with crude or refined Buriti oil was lower when compared with the control group. The same was observed for animals receiving ketogenic diet (Soares et al, 2009), the opposite behavior was induced by diet containing goat milk fat (Soares et al, 2014) and for animals receiving higher intake of flaxseed oil during pregnancy and lactation (Guarda et al, 2014).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The body weight of neonates treated with crude or refined Buriti oil was lower when compared with the control group. The same was observed for animals receiving ketogenic diet (Soares et al, 2009), the opposite behavior was induced by diet containing goat milk fat (Soares et al, 2014) and for animals receiving higher intake of flaxseed oil during pregnancy and lactation (Guarda et al, 2014).…”
Section: Discussionmentioning
confidence: 52%
“…Many experimental and clinical outcomes have shown that injuries during the critical period can change the sequence of these events, causing various and persistent effects on the NS ontogenesis. Among factors that cause injuries, the use of drugs (Deiró et al, 2008), malnutrition (Anselmo et al, 2006) and changes in quantity and quality of dietary lipids stand out (Soares et al, 2009;Santillán et al, 2010;Soares et al, 2014). Linolenic (n-3) and linoleic acids (n-6), essential fatty acids and precursors of long-chain polyunsaturated fatty acids (LCPUFAs) are among dietary lipids (Blanchard et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maternal diet with cashew nuts provided a variety of fatty acids that allowed for excellent formation of the nervous system in the offspring as shown by the results. Accelerated reflex maturation was observed in the animals treated during lactation with goat milk, which is also a source of different fatty acids (Soares et al, 2014). An opposing result was observed in a study using a maternal diet containing Buriti oil, showing retardation in reflex maturation (Medeiros et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ethological studies have been commonly conducted when investigating new substances in order to define its effects on behavior (Gauvin et al, 2016). Opposite effects have been observed when testing different substances of diet; caffeine consumption during pregnancy have been associated to delayed neuromotor development in rats (Souza et al, 2015), while a goat milk lipid diet during pregnancy have been associated to accelerated physical development and reflex maturation in rats (Soares et al, 2014). It is worthy to state that the present study is the first to observe the effects of maternal exercise before and during pregnancy on developmental behavior pattern.…”
Section: Discussionmentioning
confidence: 99%